Financial literacy as core competency of South African military officers : a measurement instrument - Van Nieuwenhuyzen, Bernard J. (Stellenbosch : University of Stellenbosch, 2009)
Thesis (PhD (School of Public Management and Planning ))—University of Stellenbosch, 2009.